Comprehensive Analysis of Expression and Prognostic Value of Sirtuins in Ovarian Cancer - Sun, Xiaodan; Wang, Shouhan; Li, Qingchang (Frontiers in Genetics, 2019)
Sirtuins (SIRTs) 1-7 are a family of intracellular enzymes, which possess nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase activity. Emerging evidence suggest that SIRTs play vital roles in tumorigenesis by regulating energy metabolism, DNA damage repair, genome stability, and other cancer-associated cellular processes. However, the distinct roles of the seven members in ovarian cancer (OC) remain elusive.The transcriptional expression patterns, prognostic values, and genetic alterations of seven SIRTs in OC patients were investigated in this study using a range of databases: Oncomine and Gene Expression Profiling Interactive Analysis (GEPIA), Kaplan-Meier Plotter, the Cancer Genome Atlas (TCGA), and cBioPortal. The protein-protein interaction (PPI) networks of SIRTs were assessed in the String database. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were analyzed in Database for Annotation, Visualization, and Integrated Discovery (DAVID). The mRNA expression levels of SIRT1–4 and 7 were downregulated while that of SIRT5 was upregulated and SIRT6 exhibited both expression dysregulation in patients with OC. Dysregulated SIRTs mRNA expression levels were associated with prognosis. Moreover, genetic alterations primarily occurred in SIRT2, 5, and 7. Network analysis indicated that SIRTs and their 20 interactors were associated with tumor-related pathways. This comprehensive bioinformatics analysis revealed that SIRT1–4, 6, and 7 may be new prognostic biomarkers while SIRT5 is a potential target for accurate therapy for patients with OC, but further studies are needed to confirm this notion. These findings will contribute to a better understanding of the distinct roles of SIRTs in OC.